Analysis of sintered WC-TIC-6CO by using powder metallurgy process - Ahmad Shahbudin, Siti Nurshahmira (2019)
Metal injection molding (MIM) is a process that combines the methods of plastic injection molding and powder metallurgy technology. In this study, the material used was tungsten carbide with 6wt% cobalt (WC-6Co) and titanium carbide (TiC) as grain growth inhibitor while low density polyethylene (LDPE) and palm stearin (PS) were used as a binder system. The sample was prepared by milling process consisting of WC-6Co at different wt. % of TiC (0.5, 0.75 and 1.0) before being mixed with binder system. The critical powder volume concentration (CPVC) obtained based on oil absorption technique is 47%. The rheological behavior was evaluated using capillary rheometer and it was conclude that all feedstock exhibit pseudoplastic behavior which is suitable to be injected where the sample with 0.75 wt. % TiC with 150ºC had the best rheological properties with activation energy of 37.68 kJ/mol, flow behavior index of 0.48 and moldability index of 1386.13. The taguchi parameter design was carried out to optimize the quality and density of the green body. The result shows the best combination parameter for minimizing warpage, shrinkage, and density value were obtained with a result of 0.0124 mm of warpage, shrinkage value improved by 33.34%, while for density, it can be inferred as improving about 1.63% which increased from 5.3968 g/cm3 to 5.48486 g/cm3. For the compaction method, WC-6Co were mixed with TiC by using ball mill mixer at 100 rpm for an hour. The characterization of the sintered samples was performed by X-ray Diffraction (XRD), Energy Dispersive Analysis (EDS), Hardness Test and Grain size analysis. The physical properties of WC-TiC-6Co was performed by using density test. At holding time 30 min, WC-0.75 wt. %TiC-6Co shows the highest density and hardness with the value of 10.2185 g/cm3 and 102.3966 HV respectively. In addition, at this composition, the grain size produced is the smallest compared to the other samples. The addition of 1.0 wt. % of TiC was not favourable as it increase the grain size while decrease the hardness value of the sintered product.